Penampilan Dua Belas Galur Padi Terpilih Hasil Persilangan dan Introduksi di Lahan Pasang Surut Bergambut - , Sutami; Fatimah Azzahra; Murjani Imberan (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2003)
Most farmers in tidal swamp areas usually grow local varieties with characteristics: adapted to tidal swamp condition, late varieties (9 to 10 month), photoperiod sensitive, very low potential yield (1 -2 ton/ha), specific grain size and accepted taste. Some farmers have grown improved varieties with high yielding ability and early maturity, but not of good adaptability to tidal swamp conditions, grain size and accepted taste. These are the reasons that the improved varieties can not establish on tidal swamp areas. The experiment was conducted on the peaty tidal swamp condition, and used 12 varieties and lines with Kapuas as control. Two lines had potential yield similar to that of the improved variety but the grain size and the taste acceptibility similar to that of local varieties. Key words: Rice, Tidal swamp